BUBBLES IN THE NORMAL AND STARBURST GALAXIES - Silich, S. A. (Одеські астрономічні публікації, 2017)
A kinetic feedback from massive stars on the interstellar medium (ISM) in normal and starburst (SB) galaxies is reviewed. Hot bubbles and expanding shells observational manifestations, and recent results from the numerical models are discussed. The possible reasons for hydrodynamic and X-ray discrepancies between the standard bubble model predictions and observations are analyzed.